The Importance of New Media Literacy in The Post-Truth Era - Onur Akyol; Cem Yücetürk (Online Academic Journal of Information Technology)
In the Post-Truth era, where people's personal values and thoughts are accepted as reality and there is no need to try to reach the truth by rational reasoning, people aim to produce, spread and have their own reality accepted by using the power of new media tools in line with their beliefs, emotions and sensitivities. Every news content produced in the media is created for an ideological or commercial purpose. In this regard, new media actors aiming to determine people's ideas and opinions use many methods such as disinformation and fake news. Therefore, in the post-truth era, it becomes even more important for users in the new media ecosystem to have new media literacy skills. This research is significant in emphasizing that individuals can only become aware of the cognitive biases preventing them from accessing the truth by developing new media literacy skills. In this study, 528 university students with different demographic characteristics were included in the study by adopting the maximum diversity sampling approach. The new media literacy levels of the participants were examined using the Relational Screening Model, which is a quantitative research design. The aim of the study is to determine which demographic characteristics significantly differ in terms of new media literacy skills. While interpreting the data, an attempt was made to prepare suggestions for the solution of the problem by making inferences about the future of the post-truth era, the social threats it may cause, and the efficiency of efforts to reduce these threats.